2007
DOI: 10.1080/14622200701488426
|View full text |Cite
|
Sign up to set email alerts
|

Cigar and smokeless tobacco use in the lesbian, gay, and bisexual population

Abstract: Large population-based studies of alternative tobacco use in the lesbian, gay, and bisexual (LGB) population are needed to more fully measure tobacco use outcomes. This descriptive study used standard measures of alternative tobacco use from two separate, statewide household-based studies to compare basic prevalence rates in the LGB population and the general population in California. A total of 1,950 adult lesbians, bisexual women, heterosexual women who have sex with women, gay men, bisexual men, and heteros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
1
8
1
Order By: Relevance
“…Current use of cigars and LCCs among LGB adults was higher than that among their HET counterparts, but the same was not observed for e-cigarettes and hookahs. Our findings were in contrast to the results from another study that found cigar use to be lower among the LGB population (Gruskin et al, 2007). Another study that used data from the 2012–2013 National Adult Tobacco Survey (NATS) examined current cigarette smoking and the use of other tobacco products (cigars, pipes, hookahs, e-cigarettes, and smokeless tobacco) by sexual identity and gender (Johnson et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Current use of cigars and LCCs among LGB adults was higher than that among their HET counterparts, but the same was not observed for e-cigarettes and hookahs. Our findings were in contrast to the results from another study that found cigar use to be lower among the LGB population (Gruskin et al, 2007). Another study that used data from the 2012–2013 National Adult Tobacco Survey (NATS) examined current cigarette smoking and the use of other tobacco products (cigars, pipes, hookahs, e-cigarettes, and smokeless tobacco) by sexual identity and gender (Johnson et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, it has been well documented that sexual minority populations experience significant disparities related to tobacco use (Balsam et al, 2012; Bennett et al, 2015; Fallin et al, 2015a; Fallin et al, 2015b; King et al, 2012; Lee et al, 2009; Rath et al, 2013). One potential mechanism that explains this disparity is that LGB individuals experience stigma and harassment, discrimination, rejection from family, and even emotional and physical violence (Balsam et al, 2012; Gruskin et al, 2007). As a result, LGB individuals experience more stress, depression, and low self-esteem than do their HET counterparts, making them more vulnerable to use substances such as tobacco.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, there is only one study on adolescent tobacco use that does not aggregate bisexuality. Fifth, only two measures of smokeless tobacco use were identified, although a recent study outside the date range of our search reports a lower prevalence of smokeless tobacco use among sexual minorities in California 84. Sixth, there is little to no evidence about the prevalence of tobacco use among sexual minority families, particularly families with children.…”
Section: Discussionmentioning
confidence: 93%
“…Although some SMW identify with a lesbian or bisexual identity, other women who have sex with women participate in same-sex relationships without identifying as "lesbian" or "bisexual." Strikingly, smoking rates among SMW are dramatically and significantly higher (at least double in most cases [48][49][50][51]) than among heterosexual peers and vary between SMW subgroups (48,52,53). Nonsmoking SMW are also significantly more likely to exhibit physiological evidence of secondhand smoke exposure (48).…”
Section: Sexual Minority Women and Respiratory Diseasementioning
confidence: 94%